Enhancement of Phosphorus Solubilization from Phosphate Rocks and Plant Nutrient Availability Through Vermicomposting - Djunita, Tengku Sabrina (2007)
Large amount of organic materials (OM), from oil palm by-products produced by plantations in Malaysia creates potential pollutants and habitat for certain parasitic insects and pathogen. Incorporation of these materials with phosphate rock (PR) and earthworm through vermicomposting process would promote the dissolution and plant availability of phosphorus (P) from PR. This study investigated the effect of oil palm by-products and earthworms in dissolution different types of PRs for production of vermiphosphocompost (VPC) in fulfilling the P requirement of Setaria splendida in comparison to the using of arbuscular mycorrhiza (AM) in a glasshouse. The potential of earthworm in using oil palm by-products was investigated by surveying the population and diversity of earthworms in oil palm plantation with different types of soils and palm tree ages. Only exotic endogeic Pontoscolex corethrurus was found in oil palm plantation with low population (0 - 42 individual m-2). Heterogeneity of earthworm population in oil palm plantation attributed to food and soil physical habitat as determined by a principal component analysis (PCA). Vermicomposting of PR mixed EFB using Eisenia fetida in the laboratory gave a higher dissolution of P with morocco PR (MPR) >gafsa PR (GPR) > togo PR (TPR) than that of normal compost system. The corresponding values for frond were 165, 52, and 30%. This was attributed to higher humic acid content in VPC (0.07 g), the population of bacteria, extractable Ca, and enzymes phosphomonoesterase in the gut of earthworm. The bacteria in EFB-earthworm intestine was identified as Pseudomonas nitroreducens, and P. citronellolis, and Cellulomonas flavigena in frond-reared earthworm. Fresh EFB contain a significant value of total extractable phenol (10 g GAE 100 g-1 extract) at the beginning of composting process and decreased gradually after 4 weeks decomposition. The compound identified in fresh EFB was 2,4-bis(1,1-dimethyl)phenol, composted and field composted EFB was 2,6- bis(1,1-dimethyl) phenol. In contrast, there was no phenol detected in vermicomposted EFB. The direct application of 3 types earthworms in the glasshouse study using Setaria grass did not gave a significant difference on P availability, total nutrients in soil, nutrient-uptake and dry matter (DM) yield of grass. The VPC showed better growth of Setaria grass compared to EFB and conventional compost. Setaria needed about 75 ton ha-1 VPC to achieve a maximum DM for this experiment Inorganic fertilizer (GPR) mixed with EFB, AM and worm enhanced Setaria grass yield (60%) compare to GPR only and by using VPC (79%). The contribution of AM, earthworm of GPR on P uptake was varied depend on the interaction among them. In conclusion, VPC is the best way to managing EFB. Its nutrients content can support Setaria growth. Improvement of Setaria grass growth and plant availability of P and other nutrients (N and K) as indicated by nutrients uptake was obtained by mixing EFB with worm, AM, and inorganic fertilizers.